CREATING A COMPUTER MODEL FOR THE SYNTHESIS OF DECODERS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The article analyzes decoders, which are a combination device that converts binary codes to decimal codes. It also compares the current schemes and truth tables of binary decoders in the absence of control inputs and in the strobe. Taking into account the need to solve the problems of analysis and synthesis in the development of combination schemes, the synthesis of the 3x8 decoder was fully disclosed, the scheme was developed and the principle of operation was explained in detail. To simulate the operation of the decoder on a computer, several software packages were analyzed, of which the mathematical package Scilab mathematical package was used to solve the problem. At the same time, the method of creating a computer-simulation model of the decoder circuit was described, and it was proved that in fact, depending on the combination of input signals, only one output of the decoder has a value of 1.
Keywords: binary code, decoder, conjunctions, disjunctors, encoder.